COMMUNICATION COMPETENCE IN AN ISLAMIC ORGANIZATION: A MALAYSIA PERSPECTIVE - Zatul Himmah Abdul Karim*; Intan Nurul ‘Ain Mohd Firdaus Kozako; Noor Rafhati Romaiha; Nur Hazwani Mohamad Roseli (International Journal of Accounting, Finance and Business, 2023)
Communication is the core element of humanity which cannot survive healthy communication channels. When a person talks to someone, it has two reasons, to inquire or inform. Communication competency refers to the extent to which a communicator achieves his or her objectives through effective and suitable contact. The main objective of this study is to review and give perspective on ways to communicate competently in an organization with good Islamic guidelines. This study used an archival method in which past studies of different researchers through online databases including the UiTM database system, as well as other databases such as Google Scholar, Science Direct, Scopus, and Emerald Insight were used, ranging from 1972 to 2021. For this study, the researchers aim to conserve as much information as possible on communication competence from the Islamic perspective. The review will give a holistic understanding of the concept to future researchers and aid in identifying the research gap in relation to this study. The findings provide a clear perspective that Islamic principles of communication competence provide an essential framework for healthy relations with everyone regardless of religion, region, nationality, or race. In addition, this study is hoped to be beneficial in understanding communication competence toward better performance in organizations in Malaysia.